Use of female-controlled dual protection methods among adolescent girls and young women living with HIV in Northern Uganda: A convergent mixed-methods study - Edward Kumakech; Deo Benyumiza; Marvin Musinguzi; Wilfred Inzama; Doryn Ebong; James Okello; Lydia Kabiri; Jasper Watson Ogwal-Okeng (PLoS ONE, 2025)
Background Adolescent girls and young women living with HIV (AGYWLHIV) in Uganda face dual risks of HIV transmission to male partners and unintended pregnancies. Male condoms require male partner cooperation. Female-controlled dual protection methods (FCDPM) offer a potential solution by enabling AGYWLHIV to independently manage their sexual and reproductive health. This study assessed the prevalence of dual protection methods (DPMs), identified factors influencing their use, and explored reasons for non-use among AGYWLHIV in northern Uganda. Methods A parallel convergent mixed-methods study was conducted among the AGYWLHIV attending antiretroviral therapy services at six public health facilities in Lira City and Lira District between November 2022 and April 2023. Participants were asked about the methods they were using to simultaneously prevent unintended pregnancy and HIV transmission. If not using any dual protection method, why not? Quantitative data on DPM prevalence and associated factors were analysed using descriptive statistics and chi-square tests, while qualitative data on non-use reasons were thematically analysed. Results Among the 423 participants (median age 22 years), no one reported using the FCDPM, while only 1.2% used any form of DPM. Male condoms alone were used by 29.3% of the participants. The few who used the DPM combined the use of the male condoms with oral contraceptive pills, emergency contraceptive pills, IUD or implants. Factors positively influencing the DPM use included marital status, prior condom use, and knowledge of safer conception methods. Barriers included personal or partner disapproval of the modern contraceptives, lack of contraceptive knowledge or misconceptions, fear of contraceptive side effects or stigma, desire to conceive, and sole reliance on the male condoms. Conclusions The findings highlight a critical gap in FCDPM uptake and the low prevalence of DPM use among AGYWLHIV. Strengthening health education on modern contraception, addressing misconceptions, and reducing fears about contraceptive side effects or stigma could improve DPM acceptance and uptake in this population.